The Implementation of Good Governance with a View to Improving the Competence of State Civil Apparatus in the Regional Government - Rahmat Salam (Budapest International Research and Critics University, 2021)
For more than twenty years, reforms that have been going on have mandated the existence of autonomy and decentralization of government to manage their areas and give the broadest possible power to self-determination. The granting of this authority is intended to improve. As one indicator to measure regional autonomy's success, the government will better serve its citizens and guide them towards a better life. The provincial government's performance has not matched the expectations, yet it has not done the community optimally. Increasing the competence of the apparatus to improve the quality of work is a determining factor in local government activities' success. The result of local government officials towards quality performance leads to the development of education, competence, and abilities because of the times' face. The competence that local government officials are expected to have is analyzing and addressing issues within the city under a realistic framework of local government.